INTERNATIONAL COMMERCIAL MEDIATION: INTERNATIONAL RECOGNITION AND ENFORCEMENT OF MEDIATION AGREEMENTS - Curlewis, Llewelyn Gray; Raubenheimer, Ettian (Obiter, 2024)
Global economic output has increased dramatically due to an increase in cross border trade, the rise of multinational corporations and globalisation. The globalisation of trade resulted in an increasing interaction between different cultures and legal traditions with different value systems and philosophical foundations, leading to increased dispute potential which could eventually develop into conflict. The default setting for conflict resolution is widely recognised as judicially sanctioned dispute resolution, otherwise referred to as litigation. Commercial litigation processes are, however, getting more costly and burdensome. Commercial disputes are furthermore becoming more complex because of the globalised trade landscape and increasing cross-border mobility. This poses unique challenges for litigants and courts. Typical problems encountered include governing law issues, enforcement issues, differing national administrative requirements and legal processes. Dispute resolution by means of litigation is subject to intrinsic characteristics exacerbating the complexity of cross-border disputes. In the EU member states for instance, it takes between one hundred and three hundred days to obtain a first- instance judgment in civil proceedings.